Pengaruh Profitabilitas, Struktur Modal, dan Ukuran Perusahaan terhadap Nilai Perusahaan: Komparasi Sebelum dan Selama Pandemi Covid-19 - Triastuty Wulandari; Leni Nur Pratiwi; Nafisah Ruhana; Rosma Pakpahan (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The entry of Covid-19 has affected many corporate sectors, especially food and beverage companies. Good management skills are needed so that companies can face all economic conditions that affect the company's financial performance. The purpose of this study is to analyze the effect of profitability prorated by ROE, firm value prorated by SIZE, and capital structure prorated by DER on firm value before and during Covid-19. This research is a quantitative study with secondary data, the number of samples is 10 food and beverage companies with financial reports for 2016-2020, so that 60 observational data are obtained uses panel regression analysis method. The results of this study indicate that partially ROE has a significant positive effect on Tobin's Q, while SIZE and DER have no significant effect on Tobin's Q before Covid-19. Meanwhile, during the Covid-19 period, ROE had a significant positive effect and DER had a significant negative effect on Tobin's Q, while SIZE had no significant effect on Tobin's Q.